An Analysis on Agile Software Development Techniques: Exploring the Concepts and Practices of Agile Software Development Techniques (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Agile improvement alludes to any innovation procedure that is lined up with the ideas of the Agile Manifesto. The Manifesto was created by a gathering fourteen driving figures in the product business, and mirrors their experience of what approaches do and don't work for software improvement.